Pluralism of Islamic Law in Aceh: Qanun Jinayat in the Framework of the Indonesian New Criminal Code - Mukhlis; Kamarusdiana Kamarusdiana; Utang Rosidin; Muhammad Iqbal; Nur Hidayahtul Nabihah Manas (AHKAM : Jurnal Ilmu Syariah, 2026)
This study analyzes normative conflicts between Aceh's Qanun Jinayat and the new Criminal Code through a legal pluralism framework. The focus centers on significant differences in criminal act formulations, juridical elements, and sanctions—particularly for khamr, adultery, and khalwat violations. Using a qualitative case study approach, this research draws on analysis of relevant legislation and in-depth interviews with Sharia Court judges and jinayat law practitioners in Aceh. The study reveals that legal pluralism in Aceh is dynamic, reflecting political tensions between central and regional authorities. Qanun Jinayat, rooted in fiqh al-jināyāt, now faces normative opposition from Article 613 of the new Criminal Code — a condition that requires systematic legal harmonization while risking the erosion of Aceh's long-held special autonomy. As an original contribution, this study proposes a "dual law enforcement" model to accommodate Aceh's religious and cultural specificities without sacrificing national legal unity. Sanctions such as caning should be replaced with rehabilitative alternatives better aligned with contemporary human rights principles. This research contributes meaningfully to the asymmetric decentralization discourse and to the understanding of the complex socio-political implications within special autonomous regions.   Abstrak Penelitian ini menganalisis konflik normatif antara Qanun Jinayat Aceh dan KUHP baru melalui kerangka teoritis pluralisme hukum. Fokus kajian tertuju pada perbedaan signifikan dalam rumusan tindak pidana, unsur-unsur yuridis, dan jenis sanksi, khususnya untuk pelanggaran khamr, zina, dan khalwat. Menggunakan metode kualitatif dengan pendekatan studi kasus, penelitian ini didukung analisis peraturan perundang-undangan relevan serta wawancara mendalam dengan hakim Mahkamah Syar'iyah dan praktisi hukum jinayat di Aceh. Studi ini mengungkapkan bahwa pluralisme hukum di Aceh bersifat dinamis, mencerminkan tarik-ulur politik antara pusat dan daerah. Qanun Jinayat yang berakar pada fikih jinayat kini menghadapi pertentangan normatif dari Pasal 613 KUHP baru — kondisi yang menuntut harmonisasi hukum sistematis sekaligus berpotensi mengikis otonomi khusus Aceh. Sebagai kontribusi orisinal, penelitian ini menawarkan model "penegakan hukum jalur ganda" untuk mengakomodasi kekhususan agama dan budaya Aceh tanpa mengorbankan persatuan dan kepastian hukum nasional. Sanksi cambuk direkomendasikan untuk dimodifikasi menjadi alternatif sanksi rehabilitatif yang lebih selaras dengan prinsip hak asasi manusia kontemporer. Penelitian ini berkontribusi penting bagi wacana desentralisasi asimetris dan pemahaman implikasi sosial-politik dalam harmonisasi hukum di daerah otonom khusus.